2005
DOI: 10.3354/meps297033
|View full text |Cite
|
Sign up to set email alerts
|

DOM fluorescence, a tracer for biogeochemical processes in a coastal upwelling system (NW Iberian Peninsula)

Abstract: ), where labile DOM is produced from phytoplankton exudation and/or lysis and (2) the bottom nepheloid layer (at a rate of about 0.2 ppb eq tryptophan d

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
66
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 59 publications
(96 reference statements)
10
66
2
Order By: Relevance
“…These fixed Ex/Em wavelengths were chosen to assure that we were measuring the same fluorophores in all samples and to allow comparison with other works. Basically, we determined the fluorescence at the wavelengths proposed by Coble et al (1990) and confirmed by Nieto-Cid et al (2005) in the Iberian upwelling system. Four replicate measurements were performed for each Ex/Em wavelength.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These fixed Ex/Em wavelengths were chosen to assure that we were measuring the same fluorophores in all samples and to allow comparison with other works. Basically, we determined the fluorescence at the wavelengths proposed by Coble et al (1990) and confirmed by Nieto-Cid et al (2005) in the Iberian upwelling system. Four replicate measurements were performed for each Ex/Em wavelength.…”
Section: Methodsmentioning
confidence: 99%
“…Four replicate measurements were performed for each Ex/Em wavelength. A four-points standard curve was prepared daily with a mixed standard of quinine sulphate (QS) and Trp in sulphuric acid 0.05 mol L 21 (Nieto-Cid et al 2005). The equivalent concentration of every peak was determined by subtracting the average peak height from the blank height and dividing by the slope of the standard curve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such fluorescent data pooled into excitation and emission matrices (EEMs) provide insights into the different types of organic compounds in DOM (Coble et al 1998;Yamashita and Tanoue 2003). In marine systems, a high concentration of protein-like FDOM is often associated with high biological activity in the surface layers (Yamashita and Tanoue 2003;Nieto-Cid et al 2005). The protein-like FDOM is often correlated with dissolved free amino acids (Yamashita and Tanoue 2003), which are readily consumed by bacterioplankton within timescale of hours to several weeks.…”
mentioning
confidence: 99%
“…The protein-like FDOM is often correlated with dissolved free amino acids (Yamashita and Tanoue 2003), which are readily consumed by bacterioplankton within timescale of hours to several weeks. Therefore, DOM fluorescence from these compounds has been used to trace dynamics of labile and semilabile organic matter in various aquatic environments (Yamashita and Tanoue 2003;Nieto-Cid et al 2005;Guillemette and del Giorgio 2011). Humic-like fluorescence is mainly due to a heterogeneous mixture of complex biopolymers (humic substances), which constitute , 30-50% of dissolved organic carbon (DOC) in aquatic systems (Thurman 1985).…”
mentioning
confidence: 99%